2000
DOI: 10.1054/jcpt.2000.18011
|View full text |Cite
|
Sign up to set email alerts
|

D-Ribose as a Supplement for Cardiac Energy Metabolism

Abstract: Metabolic support for the heart has been an attractive concept since the pioneering work of Sodi-Pallares et al. four decades ago.* Recently, interest has increased in the use of over-the-counter supplements and naturally occurring nutriceuticals for enhancement of cardiac and skeletal muscle performance. These include amino acids such as creatine, L-carnitine, and L-arginine, as well as vitamins and cofactors such as alpha-tocopherol and coenzyme Q. Like these other molecules, D-ribose is a naturally occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 41 publications
(61 reference statements)
2
44
0
Order By: Relevance
“…D-ribose is another naturally occurring five-carbon monosaccharide that is found in all living cells. It is the sugar moiety of adenosine triphosphate (ATP), therefore, it has been investigated as a potential metabolic supplement for the heart (Pauly and Pepine 2000). We have previously demonstrated that D-ribose has anti-inflammatory effects in renal ischemia/reperfusion injury (Nishiyama et al 2009;Sato et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…D-ribose is another naturally occurring five-carbon monosaccharide that is found in all living cells. It is the sugar moiety of adenosine triphosphate (ATP), therefore, it has been investigated as a potential metabolic supplement for the heart (Pauly and Pepine 2000). We have previously demonstrated that D-ribose has anti-inflammatory effects in renal ischemia/reperfusion injury (Nishiyama et al 2009;Sato et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Among familiar monosaccharides, D-ribose is a naturally occurring five-carbon monosaccharide that is found in all living cells. As it is the sugar moiety of ATP, it has been investigated as a potential metabolic supplement for the heart (Pauly and Pepine 2000). We also demonstrated that D-ribose attenuated I/R-induced renal injury by reducing neutrophil activation in normoglycemic rats (Sato et al 2009).…”
Section: Discussionmentioning
confidence: 79%
“…D-ribose is a naturally occurring fivecarbon monosaccharide that is found in all living cells. As it is the sugar moiety of ATP, it has been investigated as a potential metabolic supplement for the heart (Pauly and Pepine 2000). The inhibitory effect of activation of neutrophil of D-ribose on renal I/R is almost same potency compared with that of D-allose.…”
Section: Discussionmentioning
confidence: 99%
“…D-ribose is another naturally occurring fivecarbon monosaccharide that is found in all living cells and is cheap when compared with D-allose. As it is the sugar moiety of ATP, it has been investigated as a potential metabolic supplement for the heart (Pauly and Pepine 2000). This study was therefore designed to investigate the possi-bility that D-ribose attenuates I/R-induced renal injury by inhibiting neutrophil activation and/or infiltration.…”
mentioning
confidence: 99%